PENGARUH ASUPAN PROTEIN IBU HAMIL DAN PANJANG BADAN BAYI LAHIR TERHADAP KEJADIAN STUNTING PADA ANAK USIA 12 BULAN DI KABUPATEN BOGOR (EFFECT OF THE PREGNANT WOMEN’S PROTEIN INTAKE AND THEIR BABY LENGTH AT BIRTH TO THE INCIDENCE OF STUNTING AMONG CHILDREN - Fitrah Ernawati; Yuniar Rosamalina; Yurista Permanasari (Persagi, 2013)
ABSTRACT Nutritional adequacy of pregnant women will affect the nutritional status of their children, especially in their “golden age”. The objective of this study was to determine the associated factors that influence the incidence of stunting in children of 12 months old, to compare the hazard ratio of the occurrence of stunting, and to determine the most important factors that associated the incidence of stunting in children aged 12 months old. This was a longitudinal study. The samples include 262 pregnant women with gestational age between 12-16 weeks who were subsequently followed-up until their babies were 12 months old. Data were collected from March 2011 until December 2012. Data included maternal education, food consumption recall of pregnant women, and the nutritional status of children aged 12 months old. The statistical analysis used was descriptive analysis, Kaplan Meier, and COX Regression. Babies born from mothers who had less than 58 percent RDA protein intake in their second trimester of pregnancy had 1.6 times more risk to develop stunting at 12 months old compared to those born from mothers who had 58 % RDA or more protein intake during their second trimester of pregnancy. Also, children who were born with body length < 48 cm had 5.9 times more risk to develop stunting at 12 months old compared to those born with body length ≥ 48 cm. The protein intake of pregnant mothers at second trimester and body length of child at birth could influence the occurrence of stunting in their children at 12 months old. Keywords: child stunting, food consumption, pregnant women ABSTRAK Kecukupan gizi ibu hamil sangat mempengaruhi status gizi anak dalam kandungan yang selanjutnya akan menentukan perkembangan anak, khususnya pada masa pertumbuhan (golden age). Penelitian ini bertujuan untuk menentukan faktor yang diduga mempengaruhi kejadian postur tubuh pendek (stunting) pada anak usia 12 bulan, membandingkan rasio hazard kejadian stunting, serta menentukan faktor utama yang mempengaruhi kejadian stunting pada anak usia 12 bulan. Penelitian ini adalah penelitian longitudinal. Subjek penelitian adalah 262 ibu hamil 12-16 minggu yang mengikuti dari awal rekrutmen sampai anak lahir dan berusia 12 bulan. Data dikumpulkan dari Maret sampai Desember 2012 meliputi pendidikan ibu, konsumsi makanan 1x 24 jam, dan panjang serta berat badan lahir bayi. Panjang badan bayi diukur setiap bulan sampai bayi berusia 12 bulan. Data dianalisis dengan menggunakan analisis univariat, bivariat dengan Kaplan meier dan multivariat dengan regresi Cox. Bayi yang lahir dari ibu dengan konsumsi protein kurang dari rata-rata (< 58%AKG) pada trimesterter ke-dua mempunyai risiko 1,6 kali mengalami stunting pada usia 12 bulan, juga bayi yang lahir kurang dari 48 cm berisiko 5,9 kali mengalami stunting pada usia 12 bulan dibandingkan anak yg lahir ≥ 48 cm. Asupan protein dan status gizi saat lahir mempengaruhi kejadian stunting pada anak usia 12 bulan. [Penel Gizi Makan 2013, 36(1):1-11] Kata kunci: anak stunting, asupan zat gizi, ibu hamil